2022
DOI: 10.1039/d1ra08759b
|View full text |Cite
|
Sign up to set email alerts
|

Boosting nitrogen fertilization by a slow releasing nitrate-intercalated biocompatible layered double hydroxide–hydrogel composite loaded withAzospirillum brasilense

Abstract: Indiscriminate use of chemical fertilizers leads to soil environmental disbalance, therefore, use of environment-friendly slow-release multifunctional fertilizers are of paramount importance for sustainable crop production in the present scenario.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…44 Even though there is a bundle of literature available in connection with slow-release N and K nanocomposite fertilizers, the availability of research data for phosphorus (P) coupled with micronutrients is very much limited even in dearth. In continuation of our previous work related to slowrelease fertilizers, 45 herein a kind of Ni-ZnO cross-linked CMC based hydrogel bead was fabricated, characterized, and then used as a delivery material for the slow release of P. Notably, the prepared hydrogel beads exhibited excellent water retention capacity. The swelling kinetics were studied and fitted with different models.…”
Section: Introductionmentioning
confidence: 94%
“…44 Even though there is a bundle of literature available in connection with slow-release N and K nanocomposite fertilizers, the availability of research data for phosphorus (P) coupled with micronutrients is very much limited even in dearth. In continuation of our previous work related to slowrelease fertilizers, 45 herein a kind of Ni-ZnO cross-linked CMC based hydrogel bead was fabricated, characterized, and then used as a delivery material for the slow release of P. Notably, the prepared hydrogel beads exhibited excellent water retention capacity. The swelling kinetics were studied and fitted with different models.…”
Section: Introductionmentioning
confidence: 94%
“…The use of P-loaded LDHbiochar/hydrochar composites as P fertilizers can therefore be an effective alternative to chemical fertilizers without any negative effects on plant growth. − intercalated ZnAl-LDH composites by co-precipitation as a nitrogen SRF for crop production, 190 demonstrating 90% (w/w) and 85.45% (w/w) of intercalated NO 3…”
Section: Composite Ldhs For Phosphate Slow-releasementioning
confidence: 99%
“…Fortunately, several studies have investigated the use of LDHs as SRFs for different nutrients. Gogoi et al synthesized NO 3 – intercalated ZnAl-LDH composites by co-precipitation as a nitrogen SRF for crop production, 190 demonstrating 90% (w/w) and 85.45% (w/w) of intercalated NO 3 – at pH values of 5.25 and 7, respectively were released in 30 days. The results showed that LDHs possess the ability to supply plants with accessible N for long periods, even in acidic soils.…”
Section: Ldh-based Materials As Slow-release Fertilizersmentioning
confidence: 99%